Inferior Alveolar Nerve Injuries Following Implant Placement - Importance of Early Diagnosis and Treatment: a Systematic Review - Ilana Shavit; Gintaras Juodzbalys (Stilus Optimus, 2014)
Objectives: The purpose of this article is to systematically review diagnostic procedures and risk factors associated with inferior alveolar nerve injury following implant placement, to identify the time interval between inferior alveolar nerve injury and its diagnosis after surgical dental implant placement and compare between outcomes of early and delayed diagnosis and treatment given based on case series recorded throughout a period of 10 years. Material and Methods: We performed literature investigation through MEDLINE (PubMed) electronic database and manual search through dental journals to find articles concerning inferior alveolar nerve injury following implant placement. The search was restricted to English language articles published during the last 10 years, from December 2004 to March 2014. Results: In total, we found 33 articles related to the topic, of which 27 were excluded due to incompatibility with established inclusion criteria. Six articles were eventually chosen to be suitable. The studies presented diagnostic methods of inferior alveolar nerve sensory deficit, and we carried out an assessment of the proportion of patients diagnosed within different time intervals from the time the injury occurred. Conclusions: Various diagnostic methods have been developed throughout the years for dealing with 1 quite frequent complication in the implantology field - inferior alveolar nerve injury. Concurrently, the importance of early diagnosis and treatment was proved repeatedly. According to the results of the data analysis, a relatively high percentage of the practitioners successfully accomplished this target and achieved good treatment outcomes.